2015
DOI: 10.1111/jvim.13626
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Peak and Trough Gentamicin Concentrations in Hospitalized Horses Receiving Intravenously Administered Gentamicin

Abstract: BackgroundGentamicin is an aminoglycoside antimicrobial commonly used in horses at 6.6 mg/kg IV once daily. Therapeutic drug monitoring (TDM) can confirm desired peak concentration is reached for common bacterial isolates, and detect toxicosis associated with high trough values.ObjectivesDetermine the relationship between gentamicin dose and plasma concentration in hospitalized horses, and identify a starting dose range to achieve peaks > 32 μg/mL.AnimalsSixty‐five horses (2002–2010) receiving once‐daily genta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 26 publications
6
36
1
Order By: Relevance
“…Thus, the present study found that very few horses receiving 6.6 mg/kg IV q24h attained C 60min results considered adequate to kill bacteria with MIC ≥ 4 μg/mL as has been found previously 8. Bacterial MIC ≤2 μg/mL are very common in infections of horses sampled in ambulatory practice and would be expected to respond well to standard gentamicin dosages.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Thus, the present study found that very few horses receiving 6.6 mg/kg IV q24h attained C 60min results considered adequate to kill bacteria with MIC ≥ 4 μg/mL as has been found previously 8. Bacterial MIC ≤2 μg/mL are very common in infections of horses sampled in ambulatory practice and would be expected to respond well to standard gentamicin dosages.…”
Section: Discussionsupporting
confidence: 84%
“…Recommended target trough concentrations are variable although generally considered to be no higher than 1–2 μg/mL, although little evidence supports this concentration range 9. In the present study, and in another recent report,8 C 24h concentrations were rarely of concern, being >2 μg/mL in only 2.6% of cases, although more work needs to be done.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…These high gentamicin C peak :MIC concentrations potentiate the aminoglycoside postantibiotic effect (PAE), which is characterized by persistent suppression of bacterial growth at sub‐MIC or even undetectable gentamicin concentrations (Mueller & Boucher, ). Considering a reported gentamicin break point MIC of 2 μg/ml, for bacteria isolated from animals (Papich, ), the C peak values observed in this study result in estimated C peak :MIC ratios of 11.9 ± 1 in young adults and 13 ± 1 in aged alpacas, both well above the recommended target range of eight to 10 times MIC (Bauquier et al., ; Fraisse et al., ; Tudor, Papich, & Redding, ). For infectious organisms with intermediate susceptibility (MIC ≤4 μg/ml), the extrapolated C peak :MIC ratio of 6.0 ± 0.5 in young adults and 6.5 ± 0.5 in aged alpacas would not reach a target of 8–10 × MIC in either group.…”
Section: Discussionsupporting
confidence: 56%